Effective Internationalisation Practice in the Higher Education Institutions: A Systematic Literature Review - Udekwe, Emmanuel; Obadire, Olusegun Samson (Papanda Publisher, 2024)
Internationalisation is initiated to drive organisations' success, including higher education institutions (HEIs). This systematic literature review aims to i), determine the prevalence of existing research and publications on internationalisation practice in the HEIs, and ii), identify new practices that are reported in the scholarly literature and offer these new thoughts on the advancement of effective internationalisation practice in the HEIs. A wide-range strategy was employed to search and identify research papers from Web of Science and Scopus. The chosen papers were between the years 1994 and 2023. Out of 425 results generated, 80 publications representing 65 selected papers were chosen and themed for discussion. Investigating internationalisation in higher education is an in-depth multidisciplinary research approach that assists in determining the effect of HEIs. The findings identified challenges such as a lack of effective policy framework, decolonisation of the curriculum and digital transformation, which requires further studies on strategies for effective internationalisation practice in HEIs. Considering HEI's new focus on internationalisation, it is prudent to carry out more investigation to appreciate internationalisation’s many nuances.